RAIN WATER HARVESTING AT THE PLANTATION - Anas Arfandi; Akshari Tahir Lopa; Irma Aswani Ahmad (LPPM Universitas Negeri Jakarta, 2022)
This study aims to analyze the rainwater harvesting system and calculate the volume of rainwater that can be accommodated for water needs at the plantation site. The research method used is the Rational method. The data used are rainfall data and catchment area which are then calculated using hydrological analysis and hydraulics analysis. The calculation of the average daily rainfall uses the Gumbel method, while the calculation of rainfall intensity uses the Vanbreen method with the Talbot formula, and to find the channel discharge using the Rational method. From the results of the calculations and analysis above, it can be concluded that 1) Rainwater harvesting can be used as an alternative for managing water resources on plantations. 2) The intensity of rainfall for the 5-year return period is 30,644 mm/hour. 3) the catchment area of the garden house 2 x 13.5 m2 can produce a rainwater discharge of = 0.0000828050 m3/second. 4) The volume of 2 sewer tanks can accommodate 1570 liters of water. 5) Farmers can take advantage of stored rainwater for up to 20 days.